Hubungan Pengalaman Penyuluhan Pertolongan Pertama dengan Pengetahuan Pertolongan Pertama Cedera Ringan Teknik PRICE: Studi Korelasi pada PMR SMK YP 17 Pare - Didit Damayanti (Lembaga Pengembangan Kinerja Dosen, 2026)
First aid is the initial action taken quickly and accurately for someone who has experienced an injury. One way to improve knowledge about injury management is by providing education or counseling. This study aims to determine the relationship between first aid counseling experience and knowledge of the PRICE technique for first aid for minor injuries. The study design was correlational. The study population was 68 members of the Indonesian Red Cross (Rural Red Cross), with 30 respondents selected using a purposive sampling technique. Data were collected using a questionnaire and analyzed using the Spearman's rho test. The Spearman's rho test yielded a p-value of 0.000 (α: 0.05) with an r (correlation strength) of 0.796, indicating a significant relationship between counseling experience and knowledge of the PRICE technique for first aid for minor injuries. Experience is a valuable learning experience that can enhance one's knowledge in dealing with health problems encountered in the surrounding environment. It is recommended that respondents increase their experience in various ways to address health problems that frequently occur in daily life.